(untitled) (Global Journal of Science Frontier Research, 2015)
A device of non-classic Newton’s minorant and their graphs of functions of two real table-like variables have been introduced and a new numerical method for finding extremum of random as smooth and non-smooth functions of one real variable has been constructed.